2022
DOI: 10.1007/s13762-022-04692-w
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of selected carbon-based nanomaterials

Abstract: The widespread use of the nanomaterials increases the emission of nano-pollutants into the water. Carbon nanomaterials are particularly interesting. They are characterized by relatively stable structure, which makes them able to migrate and accumulate in the environment. Therefore, the aim of this study was to determine the potential toxicity at the different trophic levels of four selected carbon nanostructures: graphene oxide (GO), reduced graphene oxide (rGO), multi-walled carbon nanotubes (MWCNTs) and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This ensures that materials used in products, processes, or waste streams do not pose significant risks to ecosystems or human health. 130,131 Recently, Zhang et al 129 have comprehensively reviewed the ecotoxicity of mixtures of NPs and hybrid nanomaterials. Accordingly, the mixtures' combined response is primarily influenced by several factors, including: (1) the chemical composition of individual components in the mixtures, (2) the stability of suspensions containing mixed engineered NPs, (3) the type and trophic level of the tested organisms, (4) the biological level of organization, including population, communities, and ecosystems, (5) the exposure concentrations and duration, (6) the toxicity endpoint, and (7) abiotic field conditions, such as pH, ionic strength, and natural organic matter.…”
Section: Eco-toxicity Guidelines For Inherently Safe Materialsmentioning
confidence: 99%
“…This ensures that materials used in products, processes, or waste streams do not pose significant risks to ecosystems or human health. 130,131 Recently, Zhang et al 129 have comprehensively reviewed the ecotoxicity of mixtures of NPs and hybrid nanomaterials. Accordingly, the mixtures' combined response is primarily influenced by several factors, including: (1) the chemical composition of individual components in the mixtures, (2) the stability of suspensions containing mixed engineered NPs, (3) the type and trophic level of the tested organisms, (4) the biological level of organization, including population, communities, and ecosystems, (5) the exposure concentrations and duration, (6) the toxicity endpoint, and (7) abiotic field conditions, such as pH, ionic strength, and natural organic matter.…”
Section: Eco-toxicity Guidelines For Inherently Safe Materialsmentioning
confidence: 99%
“…Therefore, better removal of pollutants by the nanocomposite membranes was attributed to their lower porosity compared to pristine PES. Additionally, SWCNT-COOH and Hal are considered to be good sorbents [Gamoń et al 2022, Marszałek 2022], thus, their presence in PES-Hal and PES-SWCNT-COOH membranes enhanced the separation of organic pollutants via adsorption [Buruga et al 2019, Kamińska et al 2015.…”
Section: Wwtp Effluent Treatment Via Ultrafiltrationmentioning
confidence: 99%
“…Fluoroquinolone antibiotics such as norfloxacin, which remain in the natural environment, are difficult to transform and degrade by natural self-purification ability (Yang et al 2020). The ecotoxicity of antibiotics has also received extensive attention (Yang et al 2020, Gamoń et al 2022. Zhao et al (2016) reported that norfloxacin has high ecological risk.…”
Section: Introductionmentioning
confidence: 99%